2008
DOI: 10.1063/1.2940304
|View full text |Cite
|
Sign up to set email alerts
|

Parametrically coupled multiharmonic force imaging

Abstract: We report use of nonlinear tip-sample interactions to parametrically convert the frequency components of periodic tip-sample interaction forces to frequencies where they can be resonantly detected. One flexural mode of a cantilever is used for tapping-mode imaging and another flexural mode is used for detection of forces converted in presence of an externally injected mechanical oscillation at the difference frequency of the detecting mode and a harmonic of the tapping mode. Material contrast in attractive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…11,12 However, there is an increasing interest in the use of higher-order eigenmodes in dynamic AFM especially for applications where small tip oscillation amplitudes are desired or where multiple eigenmodes are excited simultaneously. [13][14][15][16][17][18][19] Each eigenmode has an associated dynamic stiffness ͑also known as modal stiffness͒, which is different from the static stiffness. This dynamic stiffness can be related to an equivalent spring that has the same potential energy as the eigenmode.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, there is an increasing interest in the use of higher-order eigenmodes in dynamic AFM especially for applications where small tip oscillation amplitudes are desired or where multiple eigenmodes are excited simultaneously. [13][14][15][16][17][18][19] Each eigenmode has an associated dynamic stiffness ͑also known as modal stiffness͒, which is different from the static stiffness. This dynamic stiffness can be related to an equivalent spring that has the same potential energy as the eigenmode.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Other works have demonstrated that by exciting the higher modes, especially when the tip's vibration range is small, or by exciting several dynamic modes at the same time, a high resolution can be obtained. [7][8][9][10][11][12][13] The quality of the images taken by the AFM is strongly influenced by resonant frequency and the sensitivity of higher modes. This makes the sensitivity of higher modes an important subject to be explored, and many researchers have conducted numerous studies in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in dynamic AFM methods offer the possibility of relating the measured vibration signals to the particular physical properties of the samples, such as elastic modulus, viscosity, adhesion, and chemical affinity [216]. These developments are accomplished by employing multiple excitation and detection frequencies during dynamic AFM imaging [1726]. A critical element of these mechanical measurements is the physical model being used to relate the force–distance curves to parameters representing the material properties.…”
Section: Introductionmentioning
confidence: 99%